The effect of the Jarimatika method on students’ understanding of basic mathematics at TPQ Ied Salim Al-Anzi - Sarah Amelia Azzahra; Mufti Muammarul Haq; Hasna Tsalits Tammy; Salwa Hanun Mahfuzhoh; Annisaul Khoiroh; Mishel Berlian; Muhammad Munadi Akhsani; Daffa Maulana Masykur; Fadilah Hasna Khoiriyah (Privietlab, 2026)
Mathematical competence is closely related to daily problem-solving activities, especially those involving basic numerical operations. Nevertheless, many children still encounter difficulties in mastering arithmetic concepts, mainly because mathematics is often perceived as abstract and is delivered through less interactive learning methods. This study examines the impact of the Jarimatika learning method on improving addition and subtraction skills among students at TPQ Ied Salim Al-Anzi. A quantitative research design was applied, specifically a pre-experimental model using a one-group pre-test and post-test approach. The research subjects consisted of all 13 learners at the TPQ, selected through a total sampling technique. Data collection was conducted by administering arithmetic tests before and after the application of the Jarimatika method. The hypothesis proposed that there would be a meaningful difference in students’ mathematical performance before and after the intervention. The results revealed a notable increase in the average score, from 72.31 on the pre-test to 94.62 on the post-test. Further analysis using a Paired Sample t-test yielded a t-value of –3.277 with a significance value of 0.007 (p < 0.05), indicating a statistically significant improvement. These findings suggest that the Jarimatika method effectively enhances basic arithmetic skills and can serve as an engaging and practical instructional strategy for elementary mathematics learning.